Antibacterial Activity of Tannic Acid and Tannic Acid/Amphiphilic Cationic Polymer Mixtures - Alzahrani, Fatimah M.; Yeates, Stephen G.; Webb, Michelle; Alghamdi, Hind Ali (Asian Journal of Chemistry, 2020)
In this study, the antibacterial activity of tannic acid/amphiphilic cationic polymer (poly2-[(methacryloyloxy)ethyl]trimethyl-ammonium chloride, PMADQUAT) and tannic acid mixtures was examined on the strains of Gram-positive (S. aureus) and Gram-negative (E. coli CI2, E. coli K12, Klebsiella pneumonia and P. aeruginosa) bacteria. Tannic acid exhibited the antibacterial activity against all the studied bacterial strains. The ester linkage between glucose and gallic acid is vital for the antimicrobial activity of tannic acid. Tannic acid inhibited the growth of S. aureus and E. coli K12 (1 wt%) and reduced the growth of P. aeruginosa to 23%. Mixing cationic polymers having different structures (statistical copolymer, homopolymer and diblock polymer) with tannic acid lead to an increase in antibacterial activity of tannic acid and the stability and clarity of mixtures was higher than that of a pure tannic acid solution. Tannic acid/diblock polymer and tannic acid/homopolymer mixtures (0.1 wt%) were excellent for inhibiting the growth of planktonic E. coli K12 bacteria, and a low concentration (0.0001 wt%) of tannic acid/diblock polymer reduced its growth to 19%. By contrast, the tannic acid/statistical polymer mixture (0.0001 wt%) was excellent for inhibiting the growth of Gram-positive S. aureus bacteria.